Unintended Consequences? The Effects of Neighbourhood Walkability on Crime in Nine US Cities - Wo, James C. (The British journal of criminology, 2023)
The criminological literature suggests that neighbourhood walkability might produce unintended consequences, namely that walkability is associated with higher crime rates because it affords potential offenders an abundance of weakly guarded targets. To address this proposition, we investigate linear and nonlinear effects of walkability using a sample of block groups located across nine US cities. Results from our negative binomial regression models show that an index of walkability is associated with higher crime rates and that these effects are robust across cities. We also estimate crime models that test the main effects of the four indicators which comprise the walkability index, because of the recognition that certain dimensions of walkability might have a greater impact on crime.